2019
DOI: 10.2147/oaem.s223667
|View full text |Cite
|
Sign up to set email alerts
|

<p>Perspectives On Blood-Based Point-Of-Care Diagnostics</p>

Abstract: Background: Point of Care (POC) diagnostics are an essential component of modern medicine and are employed in a variety of clinical disciplines to improve patient outcomes and provider efficiency. Despite these benefits, there are aspects of POC testing which may still hold room for improvement. In the present study, a group of healthcare professionals familiar with different facets of blood-based POC testing provided their perspectives on the benefits and challenges of POC testing within their respective fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…For this reason, follow-up, and evaluation of the preanalytical phase, which is the most vulnerable stage of TTP, can be more challenging for BGA and POCT (5). In this context, the organization of activities, symposiums, and work groups, involving other physicians, phlebotomists, and nurses, in addition to the laboratory staff as well as publishing guidelines can be beneficial for the determination of problems and finding possible solutions (6,13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, follow-up, and evaluation of the preanalytical phase, which is the most vulnerable stage of TTP, can be more challenging for BGA and POCT (5). In this context, the organization of activities, symposiums, and work groups, involving other physicians, phlebotomists, and nurses, in addition to the laboratory staff as well as publishing guidelines can be beneficial for the determination of problems and finding possible solutions (6,13).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evaluation of the Total Testing Process (TTP) of BGA, it was reported that the most problematic part was the preanalytical (prior to analysis) phase (1,4). In addition to this, it can be concluded that preanalytical phase for BGA is more vulnerable in general and poses a higher threat to patient safety as it often involves sampling and use of analyzers by non-laboratory staff (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Blood sampling is considered a minimally invasive sample when collected from finger prick collecting capillary blood and can be performed at home and at the point of care. 27 Due to the low volume of blood collected from a fingertip (less than 50 μl), the collected blood is subsequently dispended to the blood collection card for downstream analysis of the dried blood spots (DBS). 28,29 Emerging microneedle-based devices using push-button initiated capillary blood collection from the upper arm have recently been demonstrated to draw up to 100 μl of blood and generated less pain than a finger prick-based device.…”
Section: Bloodmentioning
confidence: 99%
“…The short analysis times mean that a tailor-made therapy can be carried out more quickly [ 5 ]. This has a direct influence on the patients’ chances of survival [ 5 , 7 ]. The low use of assay reagents and sample material does not only save money, but also avoids cost-intensive techniques for the collection of patient samples.…”
Section: Introductionmentioning
confidence: 99%